Delivering Proangiogenic Factors from 3D‐Printed Polycaprolactone Scaffolds for Vascularized Bone Regeneration. Issue 23 (2nd August 2020) - Liu, Haoming; Du, Yingying; Yang, Gaojie; Hu, Xixi; Wang, Lin; Liu, Bin; Wang, Jianglin; Zhang, Shengmin
Abstract: Natural bone is a highly vascularized tissue that relies on the vasculature for blood and nutrients supply to maintain skeletal integrity. Inadequacy of neovascularization may compromise the tissue ingrowth to the implanted scaffolds, and eventually results in failure for the repair. To tackle this issue and enhance self‐vascularized bone regeneration, herein a 3D biomimetic selective lasersintering (SLS) derived scaffold, with an angiogenic growth factor immobilized on its surface, that can be released in a controlled manner is proposed. To this end, a porous polycaprolactone/hydroxyapatite (PCL/HA) scaffold is prepared via the SLS technique, which is further modified with vascular endothelial growth factor (VEGF) by coprecipitation with apatite. The resultant scaffold (PCL/HA/VEGF) has an excellent cytocompatibility, and subcutaneous implantation experiment shows that the VEGF‐loaded scaffold significantly enhances the blood vessel formation compared with the VEGF‐free control. It is further demonstrated that the PCL/HA/VEGF scaffold is able to enhance the in vivo bone regeneration in a rat cranial defect model. Taken together, the current study provides not only a feasible and promising scaffold candidate to enhance the vascularized bone regeneration, but also a general strategy to overcome the inadequate vascularization issue for the repair of other tissue and organs. Abstract : Vascular endothelial growth factor (VEGF) is immobilized on selected laser‐sintered 3D scaffolds via coprecipitation under simulated physiological conditions, which is able to enhance the angiogenesis and vascularized bone repair in vivo.